Solving a Rough Interval Linear Fractional Programming problem - E. Ammar, E. Ammar; M. Muamer, M. Muamer (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, A rough interval linear fractional programming( RILFP)problem is introduced. The RILFP problemis considered by incorporating rough interval in the objective function coefficients. This proved the RILFP problem can be converted to a rough interval optimization problem with rough interval objective which is upper and lower approximations are linear fractional whose bounds. Also there is a discussion for the solutions of this kind of optimization problem. An illustrative numerical example is given for the developed theory.